First report on occurrence of Babesia infection in Nilgai Boselaphus tragocamelus from central India - B. Baviskar; K. Ingle; P. Gawande; S. Raut; K. Sirothia; A. Bhandarkar (Journal of Threatened Taxa, 2009)
A male Nilgai Boselaphus tragocamelus of approximately 6-7 years was presented for post mortem examination to the Nagpur Veterinary College, Nagpur (Maharashtra). At necropsy, the lesions observed were enlarged spleen, congestion of liver and kidney and pale mucous membranes indicating severe anaemia. Blood smears were prepared, stained with leishman’s stain which revealed Babesia sp. Organisms in the erythrocytes, which seems to be the first report in Nilgai from Central India.